2004
DOI: 10.1074/jbc.m312611200
|View full text |Cite
|
Sign up to set email alerts
|

Ordered Conformational Changes in Damaged DNA Induced by Nucleotide Excision Repair Factors

Abstract: In response to genotoxic attacks, cells activate sophisticated DNA repair pathways such as nucleotide excision repair (NER), which consists of damage removal via dual incision and DNA resynthesis. Using permanganate footprinting as well as highly purified factors, we show that NER is a dynamic process that takes place in a number of successive steps during which the DNA is remodeled around the lesion in response to the various NER factors. XPC/HR23B first recognizes the damaged structure and initiates the open… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

13
152
0

Year Published

2007
2007
2016
2016

Publication Types

Select...
6
3
1

Relationship

3
7

Authors

Journals

citations
Cited by 142 publications
(166 citation statements)
references
References 56 publications
13
152
0
Order By: Relevance
“…XPC is a subunit of the NER multi-protein machinery that facilitates DNA damage recognition (Friedberg, 2001;Riedl et al, 2003). An in vitro study suggested that binding of XPC to damaged DNA is the rate-limiting step for NER (Janicijevic et al, 2003;Tapias et al, 2004). Accumulated evidence also indicates that genetic polymorphisms of DNA repair genes such as XPA, XPC and ERCC1 are associated with increased risk of lung cancer (Mellon et al, 2002;Park et al, 2002;Marin et al, 2004;Hu et al, 2005;Suk et al, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…XPC is a subunit of the NER multi-protein machinery that facilitates DNA damage recognition (Friedberg, 2001;Riedl et al, 2003). An in vitro study suggested that binding of XPC to damaged DNA is the rate-limiting step for NER (Janicijevic et al, 2003;Tapias et al, 2004). Accumulated evidence also indicates that genetic polymorphisms of DNA repair genes such as XPA, XPC and ERCC1 are associated with increased risk of lung cancer (Mellon et al, 2002;Park et al, 2002;Marin et al, 2004;Hu et al, 2005;Suk et al, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…The basic hypothesis in the field of NER is that the mammalian DNA repair apparatus recognizes structural distortions and thermodynamic destabilization in the DNA duplex caused by the lesions, followed by a verification step that detects the presence of a chemically modified nucleobase and the excision of a fragment 24-32 nucleotides long that contains the damaged base. [3][4][5][6][7][8][9][10][11] It is now established that the first and rate-determining step in NER is the recognition of the bulky lesions by the XPC/HR23B protein heterodimer complex. 12 Since the NER machinery processes a diverse array of bulky lesions with different efficiencies, the conformational features that invoke NER are of great interest.…”
Section: Introductionmentioning
confidence: 99%
“…Several lines of evidence lead to the currently accepted hypothesis that the lesions are initially recognized by XPC with the help of UV-DDB (UV DNA damage binding protein) for cyclobutane pyrimidine dimer (CPD) lesions (17)(18)(19)(20) followed by damage verification by XPD/TFIIH (21)(22)(23)(24), XPA, and XPG (3) to finally assemble to the preincision complex (3,(25)(26)(27). This step seems to involve recruitment of the XPA protein, which is one of the proteins essential for both GG-NER and TC-NER (28).…”
mentioning
confidence: 99%